Vagrants and Vagabonds: Poverty and Mobility in the Early American Republic - O'Brassill-Kulfan, Kristin (Early American Places, 2019)
Frontmatter -- Contents -- Introduction -- 1 “She Is Doubtless a Very Vagrant”: Poverty and Mobility on the Legal Landscape -- 2 “A Wandering Life”: The Physical Landscape of Indigent Transiency -- 3 “The Removal of So Many Human Beings . . . Like Felons”: Forced Migration of the Poor -- 4 “Since He Was Free”: Vagabondage, Race, and Emancipation -- 5 “Punishment for Their Misfortunes”: Discretion, Incarceration, and Resistance -- 6 “It Was amongst the Vagrant Class . . . That Cholera Was Most Fatal”: Mobility, Poverty, and Disease -- Conclusion -- Acknowledgments -- List of Abbreviations -- Appendix -- Notes -- Index -- About the Author